Study on the performances of ANG (adsorbed natural gas) systems - Tan, Gary Heng-Liang (2018)
Global warming has been an increasing concerning over the past few decades due to the rising levels of greenhouse gasses such as carbon dioxide (CO2) and methane (CH4) as found in the atmosphere. The larger demand for fossil fuels have led to the focus on other alternative energy sources such as natural gas. These pressing global issues have resulted in growing interests in researching different porous materials such as metal organic frameworks (MOF) to store CO2 and CH4. The high cost and limitations posed by storing natural gasses using compressed natural gas (CNG) and liquefied natural gas (LNG) systems have led to the researchers to study adsorbed natural gas (ANG) systems as a potential candidate for natural gas (mainly CH4) storage. The US Department of Energy (DOE) has set a challenging target of 0.5 g/g adsorption uptake at ambient conditions. Therefore, synthesizing the right Metal MOF is crucial to achieve the DOE target. In this study, MOFs and activated carbon composite samples namely HKUST-1 and HKUST-1 with Maxsorb III will be investigated. Experiments will be conducted at the temperatures ranging from 125K to 300K and pressures of up to 10 bar to measure the gravimetric adsorption uptake for CH4. Hence the volumetric apparatus and the cryogenic setup are designed mainly for this experimental purpose. Based on the experimental results, it can be deduced that the gravimetric CH4 uptake is found to be higher at very low temperatures. However, none of the investigated samples were able to meet the DOE target at ambient conditions.